ä½¿ç”¨æŒ‡äº‹å—æ•™å¦æ–¹æ³•æé«˜MADRASAH ALIYAH DARUL ULUM é«˜ä¸äºŒå¹´çº§å¦ç”Ÿçš„è®¤å—ä¹‰èƒ½åŠ› - Melati, Della Erlita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The influence or function of the referring word to the learning of Mandarin characters is to explain the meaning of the Chinese characters. "referring" is to use the sign to point, and explain the object of the Chinese characters. Using that way for the creation of Chinese characters is called "referring word?. When learning Chinese characters, students easily forget the shape and meaning of Chinese characters. So author uses this method to assist and facilitate of second-grade students Madrasah Aliyah Darul Ulum in learning the form and meaning of Mandarin characters and prove the effect of the use of " referring word" in recognizing the meaning of Chinese characters. Through three times teaching process, the author provides the ultimate test to students. After the study, the results obtained by the author is "referring word" clearly can enhance students' knowledge in recognizing the shape and meaning of Chinese characters, it also can improve student test scores . The student's final test score is higher than the initial test score. The students initial test scores is 43.33%, and after using the referring word, the average value of the student's final test increased be 83.98%. The author takes the value of school graduation competency standard (75)/ his indicates that the use of "referring word" affect the students are able to understand the content of teaching and also know the meaning of letters Mandarin faster. Therefore, after using "referring word" to teach students the results obtained that there is an increase in learning the meaning of Mandarin characters. Keywords:   Chinese characters   Referring Word    The meaning of Chinese character